The Use of Visual Media Comics and Cartoons in Learning - Harahap, Robianna; Devianty, Rina (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This study aims to determine the criteria used for development using cartoon and comic learning media. The data used for developing cartoon media products are quantitative data and qualitative data. research results shows the development of text comic cartoon media in comic cartoons can well readable proportional layout (layout of text and images) on cartoons comics have good compatibility with the selection of backgrounds in comic cartoons the suitability of selecting fonts and font sizes in cartoon comics accuracy images used for clarity of material in suitability comic cartoons pictures with material, the presentation of the material is in order, the description of the material is very clear, visual communication, communicative, simple and engaging, creative so it can developed as a medium of learning in schools.